A novel model incorporating 3D printing for endodontic training - Dr Yi-Shing Shieh (Elsevier, 2023)
Aim or Purpose: A 3D printed model includes a tooth body, pulp cavity, and root canal system is useful in simulating clinical condition.The 3D printing method and Cone-Beam Computed Tomography (CBCT) image to create a tooth model that can be applied to various different dental training manikin. Materials and Methods: We used 3D printing to fabricate teeth obtained from CBCT image. Being installed into the model, a conductive wire was placed at the apex of the root tip where filled with solution. On the other side, a connective probe wire extended to the cheek of the human head model and was then connected with the lip hock of the electronic apex locator to form a circuit. When the probe of the electronic apex locator approaches the apex, an audible sound is produced. A bee-bee warning sound was emitted as the probe passes through the apical foramen. Therefore, the devices can simulate the actual conditions during clinical root canal treatment. Results: This device can be applied in preclinical dental student root canal therapy training, objective structured clinical examination (OSCE), endodontic specialist training and standardized training procedures. This may also integrate with dental simulation systems and develop a new training programs in dental simulation system to help our biomedical industry develop distinctive products and enhance international competitiveness. Conclusions: This model can be conveniently attached onto the dental training manikin at preclinical dental laboratory training in dental schools.